Attention disorders in normal aging, mild cognitive impairment and early Alzheimer’s disease - Τσολάκη Μ.; Κουντή Φ.; Πέτκαρη Ε.; Κιοσσέογλου Γ.; Ξανθούλης Φ.; Κάζη Ε.; Διαμαντίδου Α.; Κάζης Α.; Ευκλείδη Α. (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF